Partnering in medical education: rare disease organizations bring experts and a patient voice to the conversation. (November 2014) - Chisolm, Stephanie; Salkeld, Ellen; Houk, Alice; Huber, John
<x xml:space="preserve">Abstract</x> As new data from clinical trials and research studies are published about rare diseases, clinicians are challenged to stay abreast of the evidence, analyze it for clinical practice implications and then apply it to their medical practice. The Aplastic Anemia & MDS International Foundation (AA&MDSIF) realizes the important role our key medical advisors from the research and clinical community, as well as our patients – play in educating health-care professionals who may only occasionally see a patient with a rare bone marrow failure disease such as myelodysplastic syndromes (MDS). Patient-focused organizations can and should support medical education programs. AA&MDSIF sponsors live and web-based continuing medical education programs, provides tools to aid in diagnosis and classification of MDS, and provides free patient education resources to enable physicians, nurses, medical social workers and others to educate patients about their disease. Patient organizations have a responsibility to facilitate the delivery of rare disease-specific medical education to health-care professionals and an equal obligation to provide plain language information about our rare diseases for distribution among patients to help those patients better understand their diseases and treatment options.